Transfer of Siti Nurbaya Novel by Marah Roesli to Siti Nurbaya Theater Performance: Bayang di Balik Tiang - Mhd. Anggie Januarsyah Daulay; Russel Akbar Fauzi; Agustina Helena Samosir (BIRCU, 2022)
Siti Nurbaya's theatrical work: Bayang di Balik Tiang is an achievement of the transfer process from Marah Roesli's novel Siti Nurbaya. The creation of this theater uses transfer theory and dramatic vision as the basis for analysis. As for staging, the theory used is Stanislavski's acting theory and Bertolt Brecht's multiple sets by utilizing the essential elements of randai. The creation methods used include: production of dramatic visions, script writing, acting training, preparation of spectacles and the realization of the unity of the show. The result of this creation process is the presence of a mamak character in Siti Nurbaya's theatrical work: Bayang di Balik Tiang by utilizing the narrator's character as the embodiment of the V-effect.